(untitled) (Revista Contexto & Saúde, 2026)
Objective: to develop and validate an instrument to evaluate signs and symptoms that may occur during the process of deprescribing benzodiazepines in elderly Brazilian people. Methods: A study was carried out in three stages; the first consisted of developing an instrument to identify signs and symptoms arising from the gradual deprescription of benzodiazepines in the elderly. The instrument was created based on information from literature and from previously developed and validated scales. In the second, the instrument was validated by referees, who completed a questionnaire with seven questions, with answers scaled from 0 to 10 (Likert scale), according to the judge’s degree of agreement with the content of the instrument. They evaluated it regarding the instructions to the interviewer and the interviewee, the language of the questionnaire, clarity of statements for application by 36 health professionals, among other points. The responses to the forms were subjected to verification of agreement using the content validity coefficient (CVC). In the third stage, the understanding of the terms contained in the instrument by the target population (elderly users of primary health care) was assessed. Each of the signs and symptoms were presented to the elderly who responded regarding understanding as: “completely understands”, “partially understands” and “does not understand”. Results: The instrument was validated in the first round of evaluation by 36 reviewers (pharmacists, nurses, and physicians). All items obtained a final corrected CVC greater than 0.8. Thirty elderly individuals participated in the assessment of the instrument’s comprehension. All questions that were less understood by the elderly individuals in the comprehension assessment (such as photophobia, increased sensitivity to smell, increased sensitivity to touch, involuntary movements, among others) were updated with terms for better understanding. Conclusion: The constructed instrument was validated and approved and can be used by health professionals. It is considered that the adequate identification of the signs and symptoms of benzodiazepine deprescription will be useful in building an effective and safe process.